Remote sensing and site‐specific weed management. Issue 10 (1st December 2005) - Shaw, David R.
Abstract : Weeds typically occur in patches rather than uniformly across a field; however, conventional management practices rely on whole‐field management. Site‐specific weed management (SSWM), applying control measures only where weeds are located at densities greater than those that cause economic losses, has tremendous potential for economic and environmental benefits. Current commercially available systems can detect green vegetation and activate a herbicide spray nozzle. Researchers are actively exploring how ground‐based, aerial, or satellite sensor systems can be further developed to delineate weeds from crops during the growing season. Aerial and satellite systems can provide large‐area coverage on a regular basis, but typically do not have the spatial resolution necessary to detect small weeds among agricultural crops, which is necessary if effective control and minimized crop yield losses are to be achieved. Ground‐based systems overcome spatial resolution issues and can analyze plant shape characteristics as well as spectral profiles for weed detection. The primary limitation for ground‐based sensors is the highly complex computational capabilities and the relatively slow speeds required to allow image processing and sprayer activation in a single operation. To date, economic and technical limitations for SSWM have not favored widespread adoption. However, as research continues and technology advances, the opportunities for site‐specific control of weeds will greatly increase.